The Effect of Liquidity and Solvency on Return on Assets: Evidence from Property and Real Estate Companies Listed in the Jakarta Islamic Index 70 - Alfian; Putri Meiliana; Safwandi; Safwan Kamal (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2026)
This study aims to analyze the effect of liquidity and solvency ratios on financial performance, as measured by Return on Assets (ROA), in property and real estate companies listed on the Jakarta Islamic Index 70 (JII70) during the 2019–2024 period. The study was motivated by fluctuations in the property sector and the importance of financial management in maintaining corporate profitability. A quantitative approach was employed using secondary data obtained from the annual financial reports of selected companies. The sample consisted of eight companies selected through purposive sampling. Data were analyzed using panel data regression with the Fixed Effects Model (FEM) as the most appropriate estimation model. The results indicate that the Debt-to-Equity Ratio (DER) has a negative and significant effect on ROA. Meanwhile, the Current Ratio (CR), Cash Ratio, Debt-to-Asset Ratio (DAR), and Long-Term Debt-to-Equity Ratio (LTDER) do not individually have a significant effect on ROA. However, the simultaneous test reveals that liquidity and solvency variables collectively have a significant effect on financial performance. The adjusted R-squared value of 0.5998 indicates that approximately 59.98% of the variation in ROA can be explained by the liquidity and solvency variables included in the model, while the remaining 40.02% is influenced by other factors beyond the scope of this study. These results suggest that financial performance is not determined solely by liquidity and solvency conditions but is also affected by other internal and external factors. Therefore, maintaining an appropriate balance between liquidity and leverage is essential for improving profitability and supporting sustainable financial performance.